Novel platinum nanoclusters (Pt NCs) induce mitochondrial apoptosis and damaging autophagy for the treatment of osteosarcoma—from the perspective of P53 mutation status in different cell lines - Jialin Wang; Haodi Yue; Xin Huang; Hongjian Liu; Mengjun Zhang (NPG Asia Materials)
Abstract This study aimed to investigate the anticancer efficacy and underlying mechanism of novel platinum nanoclusters (Pt NCs) in osteosarcoma cell lines exhibiting distinct P53 expression profiles, namely MG-63 (P53−) and U2-OS (P53+). The findings revealed that Pt NCs exerted an inhibitory effect on proliferation, migration, and colony formation while promoting apoptosis in both MG-63 (P53−) and U2-OS (P53+) cells. The inhibitory effect on the malignant characteristics of MG-63 (P53−) cells was more obvious, indicating that the potential anticancer effect of Pt NCs was not dependent on P53. Animal experiments have substantiated the in vivo anticancer properties of Pt NCs, while also revealing their lower toxicity on cells and tissues. Pt NCs possess the ability to impede cell proliferation by inducing DNA damage and arresting the cell cycle in the G1 phase and possess the ability to promote BAX/Bcl-2/Caspase-3/mitochondrial apoptosis. Pt NCs may promote mitochondrial apoptosis by promoting damaging autophagy, thereby promoting cellular demise. This study has confirmed the P53-independent anticancer impact of Pt NCs on osteosarcoma in vitro and in vivo. Pt NCs may play a therapeutic role in more sensitive MG-63 (P53−) cells by promoting DNA damage to arrest the cell cycle, stimulating BAX/Bcl-2/Caspase-3/mitochondrial apoptosis, and initiating damaging autophagy.